Enhancing Village Government Performance through the Merit System: Insight from Sirna Jaya Village - Tri Rayan Abdul Malik (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
The study aimed to evaluate the implementation of the merit system in enhancing the performance of village governance in Sirna Jaya Village, Bekasi Regency, through talent management. A descriptive-qualitative research method was employed, involving interviews, documentation, and literature review to gather insights from village officials and community members. The findings revealed that the merit system's implementation was inconsistent, with recruitment and promotion not fully based on competency and performance. Talent management strategies, including training and structured development, were found lacking, resulting in underutilized potential. However, periodic monitoring and evaluation, along with a rewards system for high-performing officials, showed promising results. Despite improvements in public service delivery, significant gaps in recruitment transparency and competency-based placements remained. The study concluded that a more structured approach to talent management, equitable training distribution, and competency mapping are essential for optimizing governance performance and achieving sustainable public service improvements.